Peach rootstocks under water deficit and their characterization based on anatomical and physiological variables (Bioagro, 2020)
The lack of water is a global problem for the culture of crops. Knowing relations among intrinsic factors of how rootstocks can withstand water deficiency is important for their selection towards drought tolerance. Physiological and morphological aspects were characterized in seven genotypes of peach used as rootstocks at the following states of Mexico: Puebla (Zautla), Tlaxcala (Blanco and Amarillo), Veracruz (Jalacingo), Oaxaca (Oaxaca), State of México (Enano), Zacatecas (Zacatecas), along with the rootstock Nemaguard. One year and a half old plants were evaluated by eighteen characteristics under irrigation and drought, and analyzed by multivariable methods. The Nemaguard and Jalacingo rootstocks showed no significant differences with each other under drought conditions, while the other rootstocks were grouped according to place of origin and the irrigation condition. The principal component analysis explained 83.813 % of the total variance with three main components. The first component grouped anatomic variables (area, perimeter, major axis length, minor axis length and Feret diameter of the xylem vessels, as well as the relative conductivity of the shoot); the second component grouped physiological variables (CO2 assimilation rate, transpiration rate and stomatal conductance). By canonical discriminant analysis the evaluated rootstocks grouped Puebla (Zautla) with State of Mexico (Enano), and Zacatecas with Oaxaca, the latter two corresponding to temperate zones with low water availability. Within physiological and anatomical variables, it was possible to group the rootstocks according to their behavior under irrigation and drought.
Keywords: Assimilation rate; Prunus persica; multivariate analysis; xylem